Kedudukan Hukum yang Hidup dalam Masyarakat (Living Law) Perspektif Pasal 2 Undang Undang Nomor 1 Tahun 2023 - Fitriyah Nurrahmah; Berlian Ahsanul Husna (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2026)
The enactment of Law Number 1 of 2023 concerning the Criminal Code (KUHP) has brought a fundamental paradigm reconstruction to the Indonesian criminal justice system through the explicit recognition of the "living law" (hukum yang hidup di masyarakat). This study aims to analyze the legal standing of living law within the Indonesian legal system and examine the juridical and sociological implications of integrating these unwritten norms from the perspective of Article 2 of Law Number 1 of 2023. The research method employed is normative legal research with a statutory approach. The results indicate that the positioning of living law holds a strategic standing rooted in Article 18B paragraph (2) of the 1945 Constitution of the Republic of Indonesia and is further reinforced by the Constitutional Court Decision Number 35/PUU-X/2012. Following the promulgation of Law Number 1 of 2023, Article 2 paragraph (1) formally deconstructs the rigidity of the colonial-inherited formal legality principle (Wetboek van Strafrecht) and transforms it toward a material legality principle. Consequently, living law is now recognized as a valid basis for criminal liability and acts as a complement to national law, manifested through additional criminal penalties in the form of fulfilling local customary obligations to support restorative justice. Nonetheless, the state imposes limitations through a codification mechanism into Regional Regulations guided by Government Regulations, which must be aligned with Pancasila, the 1945 Constitution, Human Rights, and general principles of law recognized by civilized nations to prevent legal uncertainty and subjective interpretations of the law.